Geothermal Energy (IntechOpen, 2023)
Amidst the global concern over air pollutant emissions and dwindling fossil fuel reserves, geothermal energy arises as an important part of the transformation to sustainable energy systems with high reliability and flexibility. Geothermal energy is recognized as a potentially renewable energy source, immense and practically inexhaustible, clean, versatile, and useful for generating electricity, among other multiple applications. However, as in any transformation process, environmental and social impacts cannot be excluded. This book compiles scientific research from geothermal areas where environmental and social issues have been successfully addressed as an example of social, environmental, and economic equilibrium.